2016
DOI: 10.3892/ijmm.2016.2648
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of transient receptor potential vanilloid subtype 1 attenuates isoproterenol-induced myocardial fibrosis in mice

Abstract: Abstract. Transient receptor potential vanilloid subtype 1 (TRPV1) is a non-selective cation channel with high permeability to Ca 2+. Intracellular Ca 2+ signaling is an essential regulator of endothelial nitric oxide (NO) synthase (eNOS) that plays a beneficial role in myocardial fibrosis. The aim of the present study was to determine the role of TRPV1 in isoproterenol-induced myocardial fibrosis. Transgenic mice overexpressing TRPV1 were generated on a C57BL/6J genetic background. An animal model of myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…For several TRP proteins different mechanisms for their involvement in fibroblast function and fibrosis development have been proposed. In CFs from TRPV1 over-expressing mice the sustained Ca 2+ rise provoked by capsaicin is enhanced; additionally, in those mice the Isoproterenol-induced cardiac fibrosis and cardiac hypertrophy in vivo are reduced [91]. In vitro, the AngII-induced proliferation of CFs is reduced by capsaicin in cells from WT but not from TRPV1-deficient mice [92].…”
Section: Discussionmentioning
confidence: 96%
“…For several TRP proteins different mechanisms for their involvement in fibroblast function and fibrosis development have been proposed. In CFs from TRPV1 over-expressing mice the sustained Ca 2+ rise provoked by capsaicin is enhanced; additionally, in those mice the Isoproterenol-induced cardiac fibrosis and cardiac hypertrophy in vivo are reduced [91]. In vitro, the AngII-induced proliferation of CFs is reduced by capsaicin in cells from WT but not from TRPV1-deficient mice [92].…”
Section: Discussionmentioning
confidence: 96%
“…It has also been shown that capsaicin reduces fibroblast proliferation induced by AngII in vitro [173]. Moreover, overexpression of TRPV1 in transgenic mice attenuates isoproterenol-induced myocardial fibrosis [174], and the activation of TRPV1 has also been shown to be protective in a myocardial injury model [175][176][177]. On the contrary, other studies demonstrate that administration of a TRPV1 antagonist BCTC (4-(3-Chloro-2-pyridinyl)-N-[4-(1,1-dimethylethyl)phenyl]-1-piperazinecarboxamide) prevents the loss of heart function, and protects the heart from fibrosis in a pressure-overload mouse model [208].…”
Section: Trpv1 and Cardiac Fibrosismentioning
confidence: 98%
“…On the other side, genetic models provide detailed understanding of the role of various targets in understanding disease pathology. Various genetic model such as low and high level transgenic expression of β2‐adrenergic receptors related models, phosphoinositide 3‐kinase γ‐deficient mice, and overexpression of transient receptor potential vanilloid subtype 1 channel, related models have been used to study the pathophysiology of heart failure (Dorn, Tepe, Lorenz, Koch, & Liggett, ; Hasenfuss, ; Oudit et al, ; Wang, Zhang, et al, ). In the following section, the relevance of ISP as a model of MI has been detailed.…”
Section: Introductionmentioning
confidence: 99%